Nitric oxide donors increase the pregnancy rate in patients with unexplained infertility undergoing clomiphene citrate stimulation and intrauterine insemination: a randomized controlled pilot study. (4th March 2017) - Abdel Razik, Mohamed; El-Berry, Seham; El-Nezamy, Ahmed; Saad, Ahmed; Abdel Wahab, Ahmed
Abstract: This study evaluated the effects of nitric oxide donor's treatment on the pregnancy rate and uterine blood flow in patients with unexplained infertility undergoing clomiphene citrate stimulation and intrauterine insemination. A total of 120 patients were randomly allocated to a control group who received 100 mg clomiphene citrate daily from day 5 to 9 of cycle plus placebo vaginal tablets, and a study group received clomiphene citrate plus isosorbide mononitrate 10 mg vaginal tablets. Vaginal ultrasound was done before treatment and every other day starting from day 12 of cycle to count mature follicles and ovulation was triggered by IM injection of 10 000 IU hCG when one follicle measured 18 ≥ mm followed by intrauterine insemination after 36 h. The endometrial thickness, uterine arteries resistance and pulsation indices, and endometrial vascular flow and vascular flow indices were measured before treatment and at day of hCG injection. Results were analyzed after one cycle treatment using the Mean ± SD, the Student t test and the Fisher Exact test. Significant result was considered at p values <0.05. The study group had significant higher pregnancy rate/cycle, higher endometrial and lower uterine artery blood flow indices ( p  < 0.05).